Atmospheric oxygenation of the early earth and earth-like planets driven by competition between land and seafloor weathering - Yasuto Watanabe; Eiichi Tajika (Earth, Planets and Space, 2021)
Abstract Oxygen is a potential biosignature for terrestrial Earth-like planets. The primary source of oxygen on Earth is oxygenic photosynthesis, which may be limited by the supply of riverine phosphorus. Therefore, phosphorus supply from the chemical weathering of continents is crucial for the evolution of pO2. Chemical weathering occurs on both the continents and seafloor and stabilizes the climate, but phosphorus is only supplied by continental weathering. The amount of continental weathering relative to seafloor weathering may be critical for primary productivity and pO2. The area of continents could change as a result of continental growth and the amount of ocean mass on the planetary surface, and these factors could be very different on extrasolar Earth-like planets. Here, we investigated the effects of continental and seafloor weathering on the atmospheric oxygen levels, in terms of the Earth-like phosphorus-limited marine biosphere. We used a simple biogeochemical model and investigated a possible relationship between continental growth and atmospheric oxygen levels. We found that the atmosphere could evolve totally different redox conditions (an abrupt rise of atmospheric oxygen levels or a reducing condition to form organic haze) caused by continental growth, which changes the relative contribution of silicate weathering feedback from seafloor to continent. We also found that conditions with lower solar luminosity and a larger land fraction provided a preferable condition for the phosphorus-limited marine biosphere to produce high levels of oxygen in the atmosphere. We also found that the atmospheric oxygen level is strongly affected by the activity of the anaerobic marine microbial ecosystem. Our results suggest that the area of land on the planetary surface may be crucial for achieving high oxygen levels in a phosphorus-limited marine biosphere. These results contribute to the fundamental understanding of the general behaviors of Earth-like planets with oceans and an Earth-like marine biosphere.